Overview Polymorphism Gen LOX-1 3'UTR188C/T in Medan - Journal of Gadtroenterology and Hepatology - Dr.dr Shahrul Rahman, Sp.PD., Finasim (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
Overview Polymorphism Gen LOX-1 3'UTR188C/T in Medan - Journal of Gadtroenterology and Hepatology